Study of protective properties of mucous substances of psyllium and chia seeds on probiotic cultures in bread-making technology - Kryzhova, M.V.; Korniienko, I.M.; Huliaiev, V.M.; Korniienko, Y.M. (Problems of Environmental Biotechnology, 2023)
The technology of preparation of bread sourdough starter with improved functional characteristics due to the addition of psyllium and chia seeds was investigated.